Lines of flight : discursive time and countercultural desire in the work of Thomas Pynchon - Mattessich, Stefan, 1964- (Post-contemporary interventions., 2002)
An overview of the work of Pynchon and its relationship to the counterculture of the 60s, 70s and 80s.